Insights into Protein-Ionic Liquid Interactions Aiming at Macromolecule Delivery Systems - Harada, Liliam K.; Pereira, Jorge F. B. [UNESP]; Campos, Welida F.; Silva, Erica C.; Moutinho, Carla G.; Vila, Marta M. D. C.; Oliveira, Jose M.; Teixeira, Jose A.; Balcao, Victor M.; Tubino, Matthieu (Soc Brasileira Quimica, 2018)
Over the last few years, researchers have started to explore a particular class of compounds defined as ionic liquids (ILs) in attempts to use their unique characteristics. Since ILs have a very low vapor pressure, these fascinating compounds hold great potential as high performance chemicals for several applications in the (bio) pharmaceutical industry. In general, and unlike common organic solvents with comparable polarities, ILs are quite compatible with enzymes (enhancing their structural and chemical stability) and other proteins, since they can promote higher selectivities, faster reaction rates and greater enzyme stabilities in biocatalytic reactions providing, at the same time, a path for the structural and functional stabilization of protein entities. ILs appear to enhance the delivery of macromolecules, particularly protein entities, and their interactions with ILs will be tackled in detail in this review paper.
Keywords: ionic liquids; structural and functional stabilization; protein stability; biopharmaceutical applications; transdermal drug delivery